Bis(α‐hydroxycycloalkyl)phosphine Oxides Obtained from White Phosphorus via Phosphine Oxide H3PO: Synthesis, Molecular Structure, Coordination Properties and Biological Activity. Issue 5 (15th May 2020) - Gorbachuk, Elena; Badeeva, Elena; Gubaidullin, Aidar; Samigullina, Aida; Voloshina, Alexandra; Sapunova, Anastasiia; Hey‐Hawkins, Evamarie; Sinyashin, Oleg; Yakhvarov, Dmitry
Abstract: Reaction of the electrochemically in situ from elemental white phosphorus generated phosphine oxide H3 PO in a single electrochemical cell, supplied with lead cathode and aluminium anode, with cyclic ketones (cyclopentanone and cyclohexanone) results in formation of secondary phosphine oxides (bis(α‐hydroxycyclopentyl)phosphine oxide 2 a, isolated yield 15 %, and bis(α‐hydroxycyclohexyl)phosphine oxide 2 b, isolated yield 12 %) with two α‐hydroxycycloalkyl substituents at the phosphorus atom. Bis(α‐hydroxycyclopentyl)phosphine oxide reacts with [PdCl2 (COD)] (COD=1, 5‐cyclooctadiene) to give a new palladium complex trans ‐[PdCl2 P(OH)( cyclo ‐C5 H8 ‐1‐OH)2 2 ] (3 a, isolated yield 11 %) bearing phosphinous acid as a ligand formed via tautomerization of the phosphine oxide. Finally, the cytotoxicity of the synthesized secondary phosphine oxides on tumor and healthy human cell lines was studied. It was found that at a concentration of 10 −6 –10 −4 M, phosphine oxides 2 a, b exhibit similar IC50 values for the M‐Hela cell line (ca. 50 mM), but are non‐toxic for MCF‐7 cells. For human alveolar adenocarcinoma cells (A‐549), only 2 a is active (ca. 35 mM), while 2 b is not toxic. Abstract : Phosphine oxides in focus : H3 PO, generated electrochemically from P4, was used for the synthesis of secondary phosphine oxides (bis(α‐hydroxycyclopentyl)phosphine oxide and bis(α‐hydroxycyclohexyl)phosphine oxide. Bis(α‐hydroxycyclopentyl)phosphine oxide reacts with [PdCl2 (COD)] (COD=1, 5‐cyclooctadiene) to give a new palladium complex with phosphinous acid. The cytotoxicity of the synthesized secondary phosphine oxides on tumor and healthy human cell lines was studied.